Preparation, modification and environmental application of biochar: A review - Wang, Jianlong; Wang, Shizong (Journal of cleaner production, 2019)
Biochar is a carbon-rich material which can be prepared from various organic waste feedstock, such as agricultural wastes and municipal sewage sludge. Biochar has received increasing attention due to its unique feature such as high carbon content and cation exchange capacity, large specific surface area and stable structure. This review systematically analyzed and summarized the preparation, characterization, modification, and especially environmental application of biochar, based on more than 200 papers published in recent 10 year, to provide an overview of biochar with a particular on its environmental application. The physiochemical properties of biochar varies with the types of feedstocks. Pyrolysis, gasification and hydrothermal carbonization are the common methods for biochar preparation. Biochar can be modified by acid, alkali, oxidizing agents, metal ions, carbonaceous materials, steam and gas purging. The selection of modification methods depends on the environmental application fields. The biochar has been used for soil remediation and amelioration, carbon sequestration, organic solid waste composting, decontamination of water and wastewater, catalyst and activator, electrode materials and electrode modifier, which were discussed in detail. The application of biochar in the carbon sequestration should be further investigated at similar experimental conditions to obtain the consistent results. The effect of biochar on soil microbes should be further investigated to elucidate the dominant reason for the improvement of soil fertility based on different soil and feedstock. In addition, more attention should be paid to the release of heavy metals and polycyclic aromatic hydrocarbons (PAHs) from biochar to the environment when biochar is practically used for the environmental remediation. The relationship between biochar structure and activation capability should be further investigated to clarify the activation mechanism of persulfate by biochar when it is used as activator. In summary, biochar has wide application prospect in environmental remediation, and the mechanism of biochar in environmental application should be further investigated. [Display omitted] •The environmental application of biochar was systematically reviewed and analyzed.•The modification methods of biochar was summarized and compared.•Modification can be used to improve its performance for different applications.•Biochar as persulfate activator and the corresponding mechanism was discussed.•More attention should be paid to biochar stability and potential negative influence.